2020
DOI: 10.21203/rs.3.rs-112882/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Giving birth under hospital visitor restrictions: Heightened acute stress in childbirth in COVID-19 positive women

Abstract: As the novel coronavirus (COVID-19) has spread globally, a significant portion of women have undergone childbirth while possibly infected with the virus and also under social isolation due to hospital visitor restrictions. Emerging studies examined birth outcomes in COVID-19 positive women, but knowledge of the psychological experience of childbirth remains lacking. This study survey concerning childbirth and mental health launched during the first wave of the pandemic in the US. Women reporting confirmed/susp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…The majority of the studies were conducted in Europe (n=23), followed by North America (USA and Canada, n=17), then Asia (n=7), and Oceania (Australia, n=4). Seven were international studies that were conducted across three to 64 countries [30] , [35] , [36] , [37] , [38] , [39] , [40] . This review encapsulates the experiences and views of 107 support partners and 65,543 pregnant and postpartum women who gave birth during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies were conducted in Europe (n=23), followed by North America (USA and Canada, n=17), then Asia (n=7), and Oceania (Australia, n=4). Seven were international studies that were conducted across three to 64 countries [30] , [35] , [36] , [37] , [38] , [39] , [40] . This review encapsulates the experiences and views of 107 support partners and 65,543 pregnant and postpartum women who gave birth during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, some of these limitations may affect the generalisability of the findings and therefore, additional research in various cultural contexts and study designs is recommended. Finally, more research should be conducted to explore the birth experiences of COVID-19 positive women who likely experienced greater isolation, unmet expectations, and more stress during pregnancy and while giving birth [ 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Support and council should be offered to women who had adverse events during birth or who had a different birth than preferred, especially since the negative effects of unplanned operative deliveries on birth satisfaction can linger for many years. A recent study found increased incidents of acute stress when comparing COVID-19 positive women who had visitor restrictions and those who did not [ 42 , 46 ]. Therefore, special attention should be given to women who have an infectious condition during birth and might be adversely affected by hospital restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Bereits in der ersten deutschen Empfehlung vom März 2020 wird die Begleitung der Kreißenden durch eine Vertrauensperson unterstützt [6,60,61]. Das Verwehren von Unterstützung durch Begleitpersonen erhöht dabei nachweislich die mütterliche Stressbelastung unter der Geburt [62].…”
Section: Die Anwesenheit Einer Gesunden Begleitperson Unter Derunclassified